Revision of Agrilus cuprescens (Ménétriés, 1832) and related species (Coleoptera: Buprestidae) - Jendek, Eduard (Zootaxa, 2003)
The revision of Agrilus cuprescens (Ménétriés, 1832) and its relatives A. salicis Frivaldszky, 1877; A. pecirkai Obenberger, 1916; A. paludicola Krogerus, 1922 and A. ribesi Schaefer, 1946 is given. All species are illustrated. The following taxonomic changes are proposed: A. paludicola (stat. nov.) is considered as a species; A. amethystopterus Semenov-Tian-Shanskij, 1890 is considered as a subspecies of A. cuprescens (stat. nov.); A. viridis (Linné, 1758) (= rudis Abeille de Perrin, 1897 syn. nov.; = caenus Obenberger, 1924 syn. nov.); A. cuprescens cuprescens (Ménétriés) (= lacrymans Abeille de Perrin, 1895 syn. nov.; = foveolatus Abeille de Perrin, 1897 syn. nov.; = calcicola Obenberger, 1916 syn. nov.; = altaicola Obenberger, 1935 syn. nov.; = kuznecovinus Obenberger, 1936 syn. nov.). The names chalconatus Megerle and indigacellus Obenberger are unavailable. Lectotypes of 15 species are designated.